PENGARUH SIKAP KERJA DAN MOTIVASI KERJA TERHADAP KINERJA GURU DI SMA NEGERI 15 MALUKU TENGAH - Abdul Hasan Paty; Ani Rehan Sopaheluwakan (Program Studi Pendidikan Ekonomi Institut Sain dan Kependidikan (ISDIK) Kie Raha Maluku Utara, 2026)
This study aimed to examine the influence of work attitude and work motivation on teachers' performance at SMA Negeri 15 Central Maluku. Specifically, the study investigated: (1) the effect of work attitude on teachers' performance, (2) the effect of work motivation on teachers' performance, and (3) the simultaneous effect of work attitude and work motivation on teachers' performance. This research employed a quantitative approach using a causal survey design. Data were analyzed using path analysis to examine the causal relationships between the exogenous variables (work attitude and work motivation) and the endogenous variable (teachers' performance). The findings revealed that work attitude and work motivation simultaneously had a positive and significant effect on teachers' performance, as indicated by the F-test significance value of 0.000 (p < 0.05). Partial hypothesis testing also showed that work attitude had a significant effect on teachers' performance (p = 0.021 < 0.05), while work motivation demonstrated a significant positive effect with a significance value of 0.000 (p < 0.05). These findings indicate that better work attitudes and higher levels of work motivation contribute to improved teachers' performance. Therefore, enhancing teachers' work attitudes and motivation should be prioritized to improve teacher performance and the overall quality of education at SMA Negeri 15 Central Maluku.